Oral health status in patients with mucopolysaccharidoses - Ballıkaya, Elif; Eymirli, Pınar Serdar; Yıldız, Yılmaz; Avcu, Nihal; Sivri, Hatice Serap; Uzamış-Tekçiçek, Meryem (The Turkish Journal of Pediatrics, 2018)
The aim of this study is to assess oral clinical and radiological findings of patients with mucopolysaccharidoses (MPS) which are a group of rare inherited disorders of glycosaminoglycan catabolism. In this retrospective and descriptive study, records of all patients with MPS over 3 years of age managed at Division of Pediatric Metabolism, who were all referred to Department of Pediatric Dentistry for evaluation of their oral health status were assessed. Oral examinations were performed in 30 patients with determination of DMFT/S, dmft/s, dental plaque and gingival indices and panoramic radiological assessment was performed in 12 patients. Twenty-seven (90.0%) patients had dental caries and 19/21 (90.5%) had gingival inflammation. Radiological examination in 12 patients with panoramic image showed short mandibular ramus (100.0%), enlarged dental follicles (83.3%), taurodontism (75.0%), flat mandibular notch (66.7%). In association with the bone structure and morphology of the jaws, 11 patients (91.7%) had trabecular variation similar to osteoporotic disease. Condylar defect was observed in all patients, which might lead to temporomandibular joint disorders. Pulp chamber with three horns, which had never been reported in MPS before, was observed in panoramic images of 2 of 7 patients with MPS-VI. Oral clinical and radiological changes are very common in this population of MPS patients. These changes may impair opening of the mouth, eating and chewing and thus affect their quality of life. Regular dental counseling, preventive applications and dental treatments must be included in multidisciplinary team approach of MPS patients to provide better oral health.